Association of poor sleep quality and short sleep duration on the development of coronary artery disease - Bhattacharya, Debabrata; Das, Prabir Kumar; Awal, Anisul; Biswas, Trisha; Selim, G. M.; Bhattacharjee, Kalpita; Rahim, Mohammed Abdur; Hossain, Sahadat; Bhattacharya, Partha; Latif, Sayem Bin (International Journal of Research in Medical Sciences, 2025)
Background: Sleep disturbances, including poor sleep quality and short sleep duration, are strongly linked to cardiovascular disorders. However, limited data exist on the relationship between sleep parameters and coronary artery disease (CAD) in Bangladesh. This study analyzed the association of sleep quality and duration with CAD in Bangladeshi population. Methods: This case-control study was conducted in the Department of Cardiology, Chittagong Medical College Hospital. It included 139 patients hospitalized with acute coronary syndrome (ACS) as cases and 139 age-matched, healthy individuals with no CAD history as controls. Sleep quality and duration were assessed using the Pittsburgh Sleep Quality Index (PSQI), with poor sleep quality defined as a PSQI score ≥5 and short sleep duration as <6 hours. Logistic regression models, adjusted for sex and other CAD risk factors, were used to analyze the data. Results: The baseline characteristics of cases and controls were similar except for gender. Short sleep duration (<6 hours) was independently associated with CAD (Odds Ratio (OR)=2.01, 95% Confidence Interval (CI)=1.09-4.24), as was poor sleep quality (PSQI score ≥5, OR=1.89, 95% CI=1.02-3.24). Conclusions: Poor sleep quality and short sleep duration are significantly associated with CAD in Bangladeshi adults. These findings suggest that improving sleep quality and duration could serve as potential strategies for CAD prevention. Further research is warranted to explore these relationships and implement targeted interventions in this population.